WADAH MUSIK KREASI BERBASIS INDIE - Therina Adela; Fermanto Lianto (Jurusan Arsitektur dan Perencanaan, 2020)
Urban Modern Society daily activities can not be separated from all the bustle in the office, as well as at home with all the routine activities. All this daily bustle demands the people in the urban and urging them to keep working, and moving almost without them knowing the time so that there is a high possibility for the people to forget the need to rest and have a recess. As of this research are aimed to answer that needs, the people’s need to take a rest for a while, especially those people and society in Duren Tiga, an area with many offices, through the role of architecture in creating a space and place to relax in the middle of all the hustle and bustle activities. Methods used in this research are conducting a study, observation, and questionnaire for the preliminary data collection. Learning, reviewing, and observing the needs of the society, and the needs of activity as for the second step. The third is composing an architectural program suitable for the project, corresponding to the result of the observation, and answering the needs of the people so that the project’s objectives can be adequately achieved. Generally, the purpose of the project is to illustrate and define music and indie as the basic for the concept, design and activities, also for the answer to the needs of third place. Keywords: Activities; Creation; Indie; Music AbstrakKegiatan Masyarakat Kota Modern sehari-hari tidak terlepas dari segala kesibukannya dalam rutinitas di kantor maupun di rumah, dengan berbagai aktivitasnya. Kesibukan sehari-hari inilah yang menuntut masyarakat di kota modern untuk terus bekerja, bergerak, serta beraktivitas hampir tanpa mengenal waktu, sehingga sangat memungkinkan bagi mereka untuk melupakan kebutuhan akan beristirahat. Sehingga penelitian ini memiliki tujuan untuk menjawab kebutuhan masyarakat tersebut, terutama masyarakat Duren Tiga yang merupakan daerah dengan banyak perkantoran dan jasa, melalui peran arsitektur dalam menciptakan sebuah space maupun place untuk beristirahat dan bersantai di tengah kesibukan dan kepadatan aktivitas yang dijalani. Dalam penelitian ini, metode yang digunakan adalah studi, observasi dan penyebaran kuesioner sebagai pengumpulan data awal, mempelajari dan meninjau kebutuhan masyarakat dan kebutuhan aktivitas untuk melepas kejenuhan dan beristirahat sebagai tahap kedua. Ketiga, menyusun program yang dibutuhkan sesuai dengan hasil observasi, menjawab kebutuhan masyarakat sehingga tujuan proyek yang diinginkan akan tercapai dengan baik. Secara umum tujuan dari proyek ini untuk menggambarkan musik dan indie sebagai dasar perancangan dari konsep, desain serta aktivitas dan jawaban atas kebutuhan third place.